The effect of breakfast and concentration on learning achievement in physical education - Muhamad Sujanadi; Ahmad Chaeroni; Wilda Welis; Atradinal Atradinal (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines the effects of breakfast habits and concentration on learning achievement in Physical Education, Sports, and Health (PJOK) among seventh- and eighth-grade students at SMPN 1 Pariaman. Using a quantitative correlational design with an ex post facto approach, data were collected through questionnaires on breakfast habits, standardized concentration tests, and PJOK score documentation from 64 students selected via cluster random sampling. Multiple linear regression analysis showed that breakfast habits (p = 0.016) and concentration (p = 0.001) significantly influenced learning achievement individually, and together (p = 0.000) explained 30.1% of the variance. The findings indicate that regular breakfast and high concentration positively support PJOK learning outcomes.